Low-thermal-conductivity and radiation-resistant aerogel heat insulation felt and preparation method thereof
By introducing insoluble rare earth powder and sunscreen into the silicon-based aerogel composite material, and using mechanical stirring, ultrasonic impregnation tank and microwave heating, the problem of failure of traditional insulation materials under high temperature and radiation is solved, and the preparation of low-thermal conductivity and radiation-resistant aerogel thermal insulation felt is achieved, with excellent thermal insulation and radiation shielding properties.
Patent Information
- Application Number
- CN202510125976.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The insulation materials of traditional nuclear reactors are prone to irreversible embrittlement and powderization under high temperature and high energy rays, resulting in insulation failure; the traditional radiation shielding layer has weak absorption areas, which limits the application of materials.
Insoluble rare earth powder and light shielding agent are used to introduce silicon-based aerogel composite materials. The powder is evenly dispersed through mechanical stirring and ultrasonic impregnation tank technology, and the gel is quickly heated by microwave to form a low-thermal conductivity and radiation-resistant aerogel heat-insulating felt.
The low thermal conductivity and radiation resistance of the material are achieved, the high temperature thermal conductivity and production costs are reduced, and the flexibility and industrial application capabilities of the material are enhanced.
Smart Images

Figure CN119877271A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel thermal insulation materials, and specifically relates to a low thermal conductivity, radiation-resistant aerogel thermal insulation felt and a preparation method thereof. Background Art
[0002] In a nuclear reaction loop system, a thermal insulation layer is generally set up to reduce heat loss and improve energy utilization; a radiation shielding layer is also set up to prevent radioactive rays from harming the human body.
[0003] At present, traditional nuclear reactors use glass wool fiber insulation materials as insulation layers, and third-generation nuclear power plants use nuclear-grade glass wool and metal reflective insulation materials as insulation layers. The long-term high temperature and high-energy radiation of the reactor will cause the glass fiber wool to become brittle and powdery, and irreversible changes will occur, eventually leading to insulation failure. In recent years, some researchers have proposed the use of inorganic nanoporous aerogel composite materials as thermal insulation materials for nuclear reactors. The nanoparticle skeleton structure and nano-sized pore size make the aerogel have extremely low thermal conductivity, making it the solid material with the best thermal insulation performance at present. However, its radiation shielding is limited, which limits the application of this material in nuclear reactors.
[0004] Traditional radiation shielding layers mainly use materials such as lead, boron-10 and cadmium, which have weak absorption zones for rays with energies between 40-88keV. In recent years, rare earth elements have attracted strong attention because of their large thermal neutron absorption cross-section and can make up for the weak absorption zone of traditional radiation shielding layers. Researchers have proposed introducing rare earth elements into radiation shielding layers. Chinese patent publication number CN 110563435 A discloses a rare earth-based aerogel having both radiation shielding effect and thermal insulation performance and a preparation method thereof. The aerogel matrix material and the rare earth-based material are compounded to prepare a composite material combining radiation shielding and fireproof thermal insulation properties. However, the rare earth-based aerogel material in the patent has low mechanical strength and high thermal conductivity at high temperatures, making it difficult to achieve industrial application. Chinese patent publication number CN 112320833 B discloses a method for preparing a rare earth-silicon-based aerogel composite material with a surface coated with an anti-radiation coating. A soluble rare earth salt is introduced into the silicon-based aerogel composite material, and an anti-radiation rare earth coating is coated on its surface. Although this method improves the mechanical strength and high-temperature thermal insulation performance of the material, the prepared material has poor flexibility. In practical applications, it is usually necessary to coat pipes or furnace bodies, etc. The material is easily damaged and the coating falls off during bending, resulting in a decrease in the thermal insulation performance and radiation resistance of the material. In addition, mold forming is required during the preparation process of this method, which greatly increases the production cost of the material. Summary of the invention
[0005] In view of the problem that traditional thermal insulation materials in the prior art are prone to irreversible transformation after being exposed to high temperature and high-energy rays, and that traditional radiation shielding layers have weak absorption areas, the present invention provides a low thermal conductivity, radiation-resistant aerogel insulation felt and a preparation method thereof, thereby obtaining a flexible material with simple process and convenient installation, which has both thermal insulation and radiation shielding functions. The present invention introduces insoluble rare earth powder and sunscreen into silicon-based aerogel composite materials, which solves the problem that traditional thermal insulation materials fail after being exposed to high temperature and high-energy rays, and that traditional radiation shielding layers have weak absorption areas, while reducing the high-temperature thermal conductivity and cost of the material, increasing the flexibility of the material, and enabling the material to be mass-produced and industrially applied.
[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt comprises the following steps: (1) Preparation of sol: Component A: In terms of molar ratio, stir the organic silicon source: ethanol: H20 = 1: (1-3): (2-8) at 20°C-30°C for 30 minutes, then slowly add inorganic acid to adjust the solution pH to 3-6, and hydrolyze at 20°C-30°C for 2h-10h to obtain a silicon-based hydrolyzate; The organic silicon source is one of ethyl orthosilicate, methyl orthosilicate, methyl triethoxysilane, methyl trimethoxysilane, and polyethyl silicate; the inorganic acid is one of hydrochloric acid, oxalic acid, nitric acid, sulfuric acid, acetic acid, and hydrofluoric acid; Component B: by weight, ethanol: concentrated ammonia = 1kg: (0.2-2)g, stirred at room temperature for 30 minutes to obtain an alkaline catalyst solution; Component C: Stir the organic silicon source: ethanol: H20 = 1: (10-20): (2-6) at 20℃-30℃ for 30min, then slowly add inorganic acid to adjust the solution pH to 4.5-6, and add the pre-treated insoluble rare earth powder and the mixed powder of the sunscreen agent, and use mechanical stirring + compressed air at the bottom of the container to mix the sol and the powder evenly, and the stirring time is 3h-8h; The ratio of the insoluble rare earth powder and the sunscreen powder to the sol (organic silicon source + ethanol + H20 + inorganic acid) in component C is (0.5-3) kg:100L, and the particle size of the powder is 1 μm-6 μm; the mass ratio of the insoluble rare earth powder to the sunscreen powder is 1:(0.2-1); The insoluble rare earth powder is one of zirconate rare earth powder, titanate rare earth powder, tungstate rare earth powder or ceria rare earth powder; The sunscreen is one of silicon carbide, titanium dioxide, boron nitride, boron carbide and zirconium oxide; The pretreatment method of the mixed powder is: ① Rinse: rinse with anhydrous ethanol 1-3 times; ②Surface treatment: hydroxylate or alkylate the powder surface and soak the powder in surface treatment solution for 24 hours; The surface treatment solution is one of 1wt%-5wt% NaOH solution and 20wt%-50wt% methyl orthosilicate solution; (2) Prepare a whole roll of fiber felt: width 0.5m-1.5m; The fiber felt is one of glass fiber felt, high silica fiber felt, aluminum silicate fiber felt, mullite fiber felt and carbon fiber felt; (3) The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the conveyor line, and the components A, B, and C are mixed in the pipeline at a volume ratio of 1:(4-10):(0.5-2) and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; (4) The wet gel felt obtained in the above step is transported to a microwave cavity through a transport line for rapid gelation and curing by microwave heating, and the temperature in the microwave cavity is maintained at 40° C.-55° C.; (5) aging the wet gel felt after leaving the microwave cavity at room temperature for 4h-12h; (6) adding ethanol to the wet gel felt after aging at room temperature for replacement; (7) After supercritical drying of the replaced wet gel felt, a low thermal conductivity, radiation-resistant aerogel insulation felt is obtained. The obtained low thermal conductivity, radiation-resistant aerogel insulation felt has the following properties: Density: 0.16 g / cm 3 -0.19g / cm 3 , the thermal conductivity at room temperature is 0.01595W / (m·K)-0.01958W / (m·K), the thermal conductivity at 300℃ is 0.01971W / (m·K)-0.02878W / (m·K), and the thermal conductivity at 500℃ is 0.03752W / (m·K)-0.05594W / (m·K); After irradiation at 350℃ and γ-ray with cumulative dose of 1.0×10 6 After Gy irradiation, there is no change in appearance. The thermal conductivity at room temperature is 0.01602W / (m·K)-0.01619W / (m·K), the thermal conductivity at 300℃ is 0.02422W / (m·K)-0.02423 W / (m·K), and the thermal conductivity at 500℃ is 0.03789W / (m·K)-0.03799 W / (m·K).
[0007] Furthermore, the rapid gelation described in step (4) refers to a gelation time of 3 min to 8 min.
[0008] Furthermore, the supercritical drying described in step (7) is CO2 supercritical drying or ethanol supercritical drying. The CO2 supercritical drying process is as follows: the aerogel is dried under the protection of CO2 gas at a temperature of 40°C-75°C, the autoclave pressure is controlled at 8MPa-20MPa, and the reaction time is 4h-24h; the ethanol supercritical drying process is as follows: the aerogel is dried under the protection of nitrogen gas at a temperature of 260°C-320°C, the autoclave pressure is controlled at 8MPa-14MPa, and the reaction time is 4h-10h.
[0009] The present invention also relates to a low thermal conductivity, radiation-resistant aerogel insulation felt, which is obtained by using the above-mentioned method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt and has the following properties: Density: 0.16 g / cm 3 -0.19g / cm 3 , the thermal conductivity at room temperature is 0.01595W / (m·K)-0.01958W / (m·K), the thermal conductivity at 300℃ is 0.01971W / (m·K)-0.02878W / (m·K), and the thermal conductivity at 500℃ is 0.03752W / (m·K)-0.05594W / (m·K); After irradiation at 350℃ and γ-ray with cumulative dose of 1.0×10 6 After irradiation with 0.05 Gy, the appearance did not change. The thermal conductivity at room temperature was 0.01602 W / (m·K)-0.01619 W / (m·K), the thermal conductivity at 300℃ was 0.02422 W / (m·K)-0.02423 W / (m·K), and the thermal conductivity at 500℃ was 0.03789 W / (m·K)-0.03799 W / (m·K).
[0010] Compared with the prior art, the present invention has the following beneficial effects: 1. The current powder surface treatment technology is to modify the powder through a surfactant, but this method does not significantly improve the powder sedimentation and cannot achieve stable batch production. The preparation method of a low thermal conductivity, radiation-resistant aerogel insulation felt described in the present invention uses ethanol to soak to remove residual organic matter in the powder, performs surface hydroxylation or alkylation treatment to make more hydroxyl groups or alkyl groups exist on the powder surface, and then uses an organic silicon source hydrolyzate as a modifier. The organic silicon source is hydrolyzed and dehydrated and condensed with the hydroxyl groups on the powder surface. At the same time, the organic silicon sources are dehydrated and condensed with each other, so that a silicon dioxide film is formed on the powder surface to surround the powder and prevent the powder from agglomerating, so as to achieve the effect of powder dispersion; The current powder dispersion process usually uses stirring and ultrasonic vibration to disperse, but there are still problems with powder agglomeration and sedimentation. The preparation method of a low thermal conductivity, radiation-resistant aerogel insulation felt described in the present invention uses mechanical stirring + introducing compressed air from the bottom to effectively prevent the powder from settling due to the large density difference with the solvent; ultrasound is performed in an ultrasonic dipping pool during the mixing process to effectively prevent the powder from settling during the dipping process; after the fiber and the sol are mixed, the wet gel is heated in a microwave cavity to promote the rapid gelation of the wet gel felt and prevent the powder from settling during the gelation process. These two methods can promote the uniform dispersion of the powder in the aerogel felt, thereby obtaining an aerogel insulation felt with stable performance.
[0011] 2. The method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt described in the present invention adopts insoluble rare earth powder and sunscreen agent to be added into the aerogel felt. The insoluble rare earth powder has a large neutron absorption cross-section and can make up for the weak absorption area of the traditional radiation shielding layer, which can significantly improve the radiation shielding performance of the material. The sunscreen agent can improve the material's shielding effect on infrared radiation and reduce high-temperature thermal conductivity.
[0012] 3. The method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt described in the present invention has readily available raw materials, simple process, short cycle and low cost. The prepared aerogel insulation felt has good flexibility, is convenient for pipeline coating construction, and has low high-temperature thermal conductivity and good radiation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0014] Figure 1 This is a photograph of a low thermal conductivity, radiation-resistant aerogel insulation felt prepared in Example 1 of the present invention; Figure 2 This is a photograph of the appearance of the low thermal conductivity, radiation-resistant aerogel insulation felt prepared in Example 1 of the present invention before and after irradiation ( Figure 2 (a) Before irradiation; Figure 2 (b) after irradiation); Figure 3 This is a photograph of the surface morphology of the aerogel thermal insulation felt prepared in Comparative Example 3 of the present invention before and after irradiation ( Figure 3 (a) Before irradiation; Figure 3 (b) after irradiation); Figure 4 This is a scanning electron microscope photograph of the low thermal conductivity, radiation-resistant aerogel insulation felt prepared in Example 1 of the present invention before irradiation; Figure 5This is a scanning electron microscope photograph of the low thermal conductivity, radiation-resistant aerogel insulation felt prepared in Example 1 of the present invention after irradiation; Figure 6 The present invention is a flow chart for preparing the low thermal conductivity, radiation resistant aerogel thermal insulation felt. DETAILED DESCRIPTION
[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] like Figure 6 , which is a flow chart of the preparation of low thermal conductivity, radiation-resistant aerogel insulation felt according to the following embodiments; Embodiment 1: A method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt comprises the following steps: (1) Preparation of sol: Component A: In terms of molar ratio, tetraethyl orthosilicate: ethanol: H2O = 1:1:7 was stirred at 20°C for 30 min, and then nitric acid was slowly added to adjust the pH value of the solution to 4.5. After hydrolysis at 20°C for 4 h, a silicon-based hydrolyzate was obtained; Component B: by weight, ethanol: concentrated ammonia = 1kg: 1.0g, stirred at room temperature for 30 minutes to obtain an alkaline catalyst solution; Component C: Stir polyethyl silicate: ethanol: H20 = 1:20:2.5 at 20°C for 30 minutes, then slowly add nitric acid to adjust the solution pH to 4.5, and add pretreated mixed powders of lanthanum zirconate and silicon carbide titanium dioxide. Use mechanical stirring + compressed air at the bottom of the container to mix the sol and powder evenly. The stirring time is 3 hours; The ratio of the mixed powder to the sol in component C is 0.5kg:100L, and the particle size of the powder is 2μm; the mass ratio of lanthanum zirconate to silicon carbide is 1:0.5; The pretreatment method of the mixed powder is: ① Rinse: rinse twice with anhydrous ethanol; ②Surface treatment: Soak the powder in 1wt% NaOH solution for 24h; (2) Prepare a roll of glass fiber mat: width 1.5m; (3) The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the conveyor line, and the components A, B, and C are mixed in the pipeline at a volume ratio of 1:4:1.5 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; (4) The wet gel felt obtained in the above step is transported to the microwave cavity through a transport line for microwave heating for rapid gelation and curing. The gelation time is 4 minutes and the temperature in the microwave cavity is maintained at 40°C. (5) aging the wet gel felt after leaving the microwave cavity at room temperature for 6 hours; (6) adding ethanol to the wet gel felt after aging at room temperature for replacement; (7) The replaced wet gel felt is subjected to supercritical ethanol drying. The drying process is as follows: the aerogel is dried under the protection of nitrogen gas at a temperature of 260°C, the pressure of the autoclave is controlled at 10 MPa, and the reaction time is 4 h, thereby obtaining a low thermal conductivity, radiation-resistant aerogel insulation felt.
[0017] Embodiment 2: A method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt comprises the following steps: (1) Preparation of sol: Component A: Based on the molar ratio, stir polyethyl silicate: ethanol: H20 = 1:3:2 at 30°C for 30 min, then slowly add sulfuric acid to adjust the solution pH to 3, and hydrolyze at 30°C for 2 h to obtain a silicon-based hydrolyzate; Component B: by weight, ethanol: concentrated ammonia = 1kg: 0.2g, stirred at room temperature for 30 minutes to obtain an alkaline catalyst solution; Component C: Stir methyl orthosilicate: ethanol: H20 = 1:10:6 at 20-30°C for 30 minutes, then slowly add sulfuric acid to adjust the solution pH to 6, and add the pre-treated mixed powder of gadolinium titanate and titanium dioxide, and use mechanical stirring + compressed air at the bottom of the container to mix the sol and powder evenly, and the stirring time is 4 hours; The ratio of the mixed powder to the sol in component C is 2kg:100L, and the particle size of the powder is 3μm; the mass ratio of gadolinium titanate to titanium dioxide is 1:1; The pretreatment method of the mixed powder is: ① Rinse: rinse twice with anhydrous ethanol; ②Surface treatment: Soak the powder in 2wt% NaOH solution for 24h; (2) Prepare a whole roll of high silica fiber felt: width 1.5m; (3) The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the conveyor line, and the components A, B, and C are mixed in the pipeline at a volume ratio of 1:7:0.5 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; (4) The wet gel felt obtained in the above step is transported to the microwave cavity through a transport line for microwave heating for rapid gelation and curing. The gelation time is 5 minutes and the temperature in the microwave cavity is maintained at 45°C. (5) aging the wet gel felt after leaving the microwave cavity at room temperature for 4 hours; (6) adding ethanol to the wet gel felt after aging at room temperature for replacement; (7) The replaced wet gel felt is subjected to supercritical ethanol drying. The drying process is as follows: the aerogel is dried under the protection of nitrogen gas at a temperature of 280°C, the pressure of the autoclave is controlled at 8 MPa, and the reaction time is 6 h, thereby obtaining a low thermal conductivity, radiation-resistant aerogel insulation felt.
[0018] Embodiment 3: A method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt comprises the following steps: (1) Preparation of sol: Component A: Based on the molar ratio, stir polyethyl silicate: ethanol: H20 = 1:2:6 at 25°C for 30 minutes, then slowly add oxalic acid to adjust the solution pH to 5, and hydrolyze at 25°C for 8 hours to obtain a silicon-based hydrolyzate; Component B: by weight, ethanol: concentrated ammonia = 1kg: 2g, stirred at room temperature for 30 minutes to obtain an alkaline catalyst solution; Component C: Stir methyl orthosilicate: ethanol: H20 = 1:15:3 at 20-30°C for 30 minutes, then slowly add oxalic acid to adjust the solution pH to 6, and add the pre-treated mixed powder of gadolinium cerate and boron carbide, and use mechanical stirring + compressed air at the bottom of the container to mix the sol and powder evenly, and the stirring time is 4 hours; The ratio of the mixed powder to the sol in component C is 0.8kg:100L, and the particle size of the powder is 6μm; the mass ratio of gadolinium cerate to boron carbide is 1:0.2; The pretreatment method of the mixed powder is: ① Rinse: rinse twice with anhydrous ethanol; ②Surface treatment: Soak the powder in 5wt% NaOH solution for 24h; (2) Prepare a full roll of glass fiber felt: width 1.5m; (3) The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the conveyor line, and the components A, B, and C are mixed in the pipeline at a volume ratio of 1:10:2 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; (4) The wet gel felt obtained in the above step is transported to the microwave cavity through a transport line for microwave heating for rapid gelation and curing. The gelation time is 7 minutes and the temperature in the microwave cavity is maintained at 50°C. (5) aging the wet gel felt after leaving the microwave cavity at room temperature for 7 hours; (6) adding ethanol to the wet gel felt after aging at room temperature for replacement; (7) The replaced wet gel felt is subjected to supercritical ethanol drying. The drying process is as follows: the aerogel is protected by nitrogen gas, the drying temperature is 300°C, the pressure of the autoclave is controlled at 14 MPa, and the reaction time is 4 hours, thereby obtaining a low thermal conductivity, radiation-resistant aerogel insulation felt.
[0019] Embodiment 4: A method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt comprises the following steps: (1) Preparation of sol: Component A: In terms of molar ratio, methyltrimethoxysilane: ethanol: H20 = 1:3:8 was stirred at 30°C for 30 min, and then hydrofluoric acid was slowly added to adjust the pH value of the solution to 3.5. After hydrolysis at 20°C for 10 h, a silicon-based hydrolyzate was obtained; Component B: by weight, ethanol: concentrated ammonia = 1kg: 1.5g, stirred at room temperature for 30 minutes to obtain an alkaline catalyst solution; Component C: Stir ethyl orthosilicate: ethanol: H20 = 1:12:4 at 20-30°C for 30 minutes, then slowly add hydrofluoric acid to adjust the solution pH to 5, and add the pre-treated mixed powder of yttrium tungstate and zirconium oxide, and use mechanical stirring + compressed air at the bottom of the container to mix the sol and powder evenly, and the stirring time is 4 hours; The ratio of the mixed powder to the sol in component C is 1.5kg:100L, and the particle size of the powder is 1 μm; the mass ratio of gadolinium cerate to boron carbide is 1:0.7; The pretreatment method of the mixed powder is: ① Rinse: rinse with anhydrous ethanol 3 times; ②Surface treatment: Soak the powder in 50wt% methyl orthosilicate ethanol solution for 24h; (2) Prepare a full roll of mullite fiber felt: width 0.5m; (3) The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the conveyor line, and the components A, B, and C are mixed in the pipeline at a volume ratio of 1:8:1 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; (4) The wet gel felt obtained in the above step is transported to the microwave cavity through a transport line for microwave heating for rapid gelation and curing. The gelation time is 8 minutes and the temperature in the microwave cavity is maintained at 40°C. (5) aging the wet gel felt after leaving the microwave cavity at room temperature for 12 hours; (6) adding ethanol to the wet gel felt after aging at room temperature for replacement; (7) The replaced wet gel felt is subjected to CO2 supercritical drying. The drying process is as follows: the aerogel is dried under the protection of nitrogen gas at a temperature of 50°C, the pressure of the autoclave is controlled at 12 MPa, and the reaction time is 12 h, thereby obtaining a low thermal conductivity, radiation-resistant aerogel insulation felt.
[0020] Embodiment 5: A method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt comprises the following steps: (1) Preparation of sol: Component A: Based on the molar ratio, methyltriethoxysilane: ethanol: H20 = 1:3:4 was stirred at 30°C for 30 min, and then acetic acid was slowly added to adjust the pH value of the solution to 6. After hydrolysis at 20°C for 8 h, a silicon-based hydrolyzate was obtained; Component B: by weight, ethanol: concentrated ammonia = 1kg: 1.2g, stirred at room temperature for 30 minutes to obtain an alkaline catalyst solution; Component C: Stir ethyl orthosilicate: ethanol: H20 = 1:15:2 at 20-30°C for 30 minutes, then slowly add acetic acid to adjust the solution pH to 5, and add the pre-treated mixed powder of yttrium zirconate and titanium dioxide, and use mechanical stirring + compressed air at the bottom of the container to mix the sol and powder evenly, and the stirring time is 8 hours; The ratio of the mixed powder to the sol in component C is 3kg:100L, and the particle size of the powder is 1 μm; the mass ratio of yttrium zirconate to titanium dioxide is 1:0.4; The pretreatment method of the mixed powder is: ① Rinse: rinse with anhydrous ethanol 3 times; ②Surface treatment: Soak the powder in 20wt% methyl orthosilicate ethanol solution for 24h; (2) Prepare a whole roll of aluminum silicate fiber felt: width 0.6m; (3) The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the conveyor line, and the components A, B, and C are mixed in the pipeline at a volume ratio of 1:6:0.8 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; (4) The wet gel felt obtained in the above step is transported to the microwave cavity through a transport line for microwave heating for rapid gelation and curing. The gelation time is 3 minutes and the temperature in the microwave cavity is maintained at 55°C. (5) aging the wet gel felt after leaving the microwave cavity at room temperature for 12 hours; (6) adding ethanol to the wet gel felt after aging at room temperature for replacement; (7) The replaced wet gel felt is subjected to CO2 supercritical drying. The drying process is as follows: the aerogel is protected by nitrogen gas, the drying temperature is 60°C, the pressure of the autoclave is controlled at 14 MPa, and the reaction time is 8 hours, thereby obtaining a low thermal conductivity, radiation-resistant aerogel insulation felt.
[0021] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that in step (1): ①Preparation of sol: Component A: In terms of molar ratio, stir ethyl orthosilicate: ethanol: H20 = 1:1:7 at 20°C for 30 minutes, then slowly add nitric acid to adjust the solution pH to 4.5, and hydrolyze at 20°C for 4 hours to obtain a silicon-based hydrolyzate; add the surfactant sodium dodecylbenzene sulfonate to the silicon-based hydrolyzate and stir evenly, then add the mixed powder of lanthanum zirconate and titanium dioxide to the hydrolyzate and stir evenly. The mass ratio of sodium dodecylbenzene sulfonate to the hydrolyzate is 1:100, the ratio of the mixed powder to the hydrolyzate is 1kg:167L, and the powder particle size is 2μm; the mass ratio of lanthanum zirconate to silicon carbide is 1:0.5; Component B: by weight, ethanol: concentrated ammonia = 1kg: 1.0g, stirred at room temperature for 30 minutes to obtain an alkaline catalyst solution; ② Prepare a whole roll of glass fiber mat: width 1.5m; ③ The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the transport line, and the A component and the B component are mixed in the pipeline at a volume ratio of 2.5:4 and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; The other steps are consistent with those in Example 1.
[0022] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that only mechanical stirring is used to evenly mix the sol and the powder, there is no ultrasound in the dipping pool, there is no microwave cavity for heating on the conveying line, and the gel time is 10 minutes.
[0023] The other steps are consistent with those in Example 1.
[0024] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that no mixed powder is added, and the rest is the same as Example 1.
[0025] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that silicon carbide is not added, and the rest is the same as Example 1.
[0026] Performance Test: The thermal insulation felts prepared in the examples and comparative examples were subjected to performance tests: Density: Tested according to GB / T34336-2017.
[0027] Room temperature thermal conductivity test: Tested according to GB / T10295-2008.
[0028] 300℃ / 500℃ thermal conductivity test: Tested according to GB / T10294-2008, the results are shown in Table 1: Table 1: Thermal insulation felt performance test table
[0029] The low thermal conductivity and radiation-resistant aerogel insulation felt obtained in Example 1 and Comparative Example 3, and the aerogel insulation felt without rare earth and sunscreen added were placed in an irradiation box (temperature 350°C, γ-ray irradiation dose 1×10 6 After the test of (Gy), the properties of the composite materials before and after the irradiation are shown in Table 2: Table 2: Performance test table of thermal insulation felt before and after irradiation
[0030] A roll (37.5 m2) of low thermal conductivity, radiation-resistant aerogel insulation felt obtained in Example 1, Comparative Example 1 and Comparative Example 2 was prepared. 2 ) Randomly select 4 groups of samples, and test the properties of the composite materials as shown in Table 3: Table 3: Thermal insulation felt performance stability test table
[0031] Result analysis: Figure 1 is a photograph of the low thermal conductivity, radiation-resistant aerogel insulation felt prepared in Example 1; Figure 2 is a photograph of the surface morphology of the low thermal conductivity, radiation-resistant aerogel insulation felt prepared in Example 1 of the present invention before and after irradiation, wherein Figure 2 (a) before irradiation, Figure 2 (b) after irradiation; by comparing Example 1 with Comparative Examples 1-2 (Table 3), the performance of the sample in Example 1 is stable, while Comparative Examples 1-2 use surfactants to modify the powder or use traditional preparation processes for dispersion to prepare materials with excellent thermal conductivity, but the performance stability of the prepared materials is poor. This is because the traditional powder modification and dispersion process still causes the powder to settle, resulting in uneven distribution of the powder inside the material. Figure 4This is a scanning electron microscope photograph of the low thermal conductivity, radiation-resistant aerogel insulation felt prepared in Example 1 before irradiation. It can be seen that in Example 1, ethanol is used to soak the powder to remove residual organic matter, and then the surface is hydroxylated to allow more hydroxyl groups to exist on the surface of the powder. Then, an organic silicon source hydrolyzate is used as a modifier to hydrolyze the organic silicon source and dehydrate and condense with the hydroxyl groups on the surface of the powder. At the same time, the organic silicon sources dehydrate and condense with each other, so that a silicon dioxide film is formed on the surface of the powder to surround the powder and prevent the powder from agglomerating. Figure 5 This is a scanning electron microscope photograph of the low thermal conductivity, radiation-resistant aerogel insulation felt prepared in Example 1 after irradiation. It can be seen that Example 1 combines mechanical stirring + bottom compressed air to disperse the powder, which can effectively prevent the powder from settling due to the large density difference with the solvent; ultrasound is performed in the ultrasonic dipping pool during the mixing process, which can effectively prevent the powder from settling during the dipping process; after the fiber and the sol are mixed, the wet gel is heated in a microwave cavity to promote the rapid gelation of the wet gel felt, which can prevent the powder from settling during the gelation process. The original powder surface modification method, dispersion process, and preparation process of the present invention can promote the uniform dispersion of the powder in the aerogel felt, thereby obtaining an aerogel insulation felt with stable performance.
[0032] By comparing the embodiment with comparative examples 3-4, the addition of the sunscreen in the embodiment can effectively inhibit high-temperature radiation heat transfer and improve the high-temperature thermal insulation performance of the aerogel composite material.
[0033] Figure 3 The following are photos of the surface morphology of the aerogel thermal insulation felt prepared in Comparative Example 3 before and after irradiation: Figure 3 (a) before irradiation, Figure 3 (b) after irradiation; by comparing the results before and after irradiation of Example 1 and Comparative Example 3 (Table 2), the apparent morphology of the thermal insulation felt prepared in Example 1 before and after irradiation is basically unchanged (see Figure 2 ), the room temperature thermal conductivity and high temperature thermal conductivity are basically the same before and after irradiation. However, the appearance of the thermal insulation felt prepared in comparative example 3 after irradiation showed obvious shrinkage and severe cracking (see Figure 3 ), its thermal conductivity cannot be detected due to severe cracking. From the SEM photo (see Figure 4 and Figure 5 ) It can also be seen that the fiber and aerogel morphology of the thermal insulation felt prepared in Example 1 are basically the same before and after irradiation, and the pore size and skeleton particle size have not changed. The above results show that the insoluble rare earth powder and sunscreen are added to the aerogel felt. The insoluble rare earth powder has a large neutron absorption cross section and can make up for the weak absorption area of the traditional radiation shielding layer, which can significantly improve the radiation shielding performance of the material. The sunscreen can improve the shielding effect of the material on infrared radiation and significantly reduce the high-temperature thermal conductivity of the material.
[0034] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt, characterized in that: The following steps are involved: (1) Preparation of sol: Component A: In terms of molar ratio, stir the organic silicon source: ethanol: H20 = 1: (1-3): (2-8) at 20°C-30°C for 30 minutes, then slowly add inorganic acid to adjust the solution pH to 3-6, and hydrolyze at 20°C-30°C for 2h-10h to obtain a silicon-based hydrolyzate; The organic silicon source is one of ethyl orthosilicate, methyl orthosilicate, methyl triethoxysilane, methyl trimethoxysilane, and polyethyl silicate; the inorganic acid is one of hydrochloric acid, oxalic acid, nitric acid, sulfuric acid, acetic acid, and hydrofluoric acid; Component B: by weight, ethanol: concentrated ammonia = 1kg: (0.2-2)g, stirred at room temperature for 30 minutes to obtain an alkaline catalyst solution; Component C: Stir the organic silicon source: ethanol: H20 = 1: (10-20): (2-6) at 20℃-30℃ for 30min, then slowly add inorganic acid to adjust the solution pH to 4.5-6, and add the pre-treated insoluble rare earth powder and the mixed powder of the sunscreen agent, and use mechanical stirring + compressed air at the bottom of the container to mix the sol and the powder evenly, and the stirring time is 3h-8h; The ratio of the insoluble rare earth powder to the sunscreen powder to the sol in the C component is (0.5-3) kg:100 L, and the powder particle size is 1 μm-6 μm; the mass ratio of the insoluble rare earth powder to the sunscreen powder is 1:(0.2-1); the sol is an organic silicon source + ethanol + H2O + inorganic acid; The insoluble rare earth powder is one of zirconate rare earth powder, titanate rare earth powder, tungstate rare earth powder or ceria rare earth powder; The sunscreen is one of silicon carbide, titanium dioxide, boron nitride, boron carbide and zirconium oxide; The pretreatment method of the mixed powder is: ① Rinse: rinse with anhydrous ethanol 1-3 times; ②Surface treatment: hydroxylate or alkylate the powder surface and soak the powder in surface treatment solution for 24 hours; The surface treatment solution is one of 1wt%-5wt% NaOH solution and 20wt%-50wt% methyl orthosilicate ethanol solution; (2) Prepare a whole roll of fiber felt: width 0.5m-1.5m; The fiber felt is one of glass fiber felt, high silica fiber felt, aluminum silicate fiber felt, mullite fiber felt and carbon fiber felt; (3) The fiber felt roll passes through the ultrasonic immersion tank at a uniform speed through the conveyor line, and the components A, B, and C are mixed in the pipeline at a volume ratio of 1:(4-10):(0.5-2) and then sprayed into the ultrasonic immersion tank to mix the fiber and the sol to obtain a wet gel felt; (4) The wet gel felt obtained in the above step is transported to a microwave cavity through a transport line for rapid gelation and curing by microwave heating, and the temperature in the microwave cavity is maintained at 40° C.-55° C.; (5) aging the wet gel felt after leaving the microwave cavity at room temperature for 4h-12h; (6) adding ethanol to the wet gel felt after aging at room temperature for replacement; (7) After supercritical drying of the replaced wet gel felt, a low thermal conductivity, radiation-resistant aerogel insulation felt is obtained. The obtained low thermal conductivity, radiation-resistant aerogel insulation felt has the following properties: Density: 0.16 g / cm 3 -0.19g / cm 3 , the thermal conductivity at room temperature is 0.01595W / (m·K)-0.01958W / (m·K), the thermal conductivity at 300℃ is 0.01971W / (m·K)-0.02878W / (m·K), and the thermal conductivity at 500℃ is 0.03752W / (m·K)-0.05594W / (m·K); After irradiation at 350℃ and γ-ray with cumulative dose of 1.0×10 6 After Gy irradiation, there is no change in appearance. The thermal conductivity at room temperature is 0.01602W / (m·K)-0.01619W / (m·K), the thermal conductivity at 300℃ is 0.02422W / (m·K)-0.02423 W / (m·K), and the thermal conductivity at 500℃ is 0.03789W / (m·K)-0.03799 W / (m·K).
2. The method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt according to claim 1, characterized in that: The volume concentration of ethanol in step (1) and step (6) is ≥95%.
3. The method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt according to claim 1, characterized in that: The rapid gelation described in step (4) refers to a gelation time of 3 min to 8 min.
4. The method for preparing a low thermal conductivity, radiation-resistant aerogel insulation felt according to claim 1, characterized in that: The supercritical drying described in step (7) is CO2 supercritical drying or ethanol supercritical drying. The CO2 supercritical drying process is as follows: the aerogel is dried under the protection of CO2 gas at a temperature of 40°C-75°C, the autoclave pressure is controlled at 8MPa-20MPa, and the reaction time is 4h-24h; the ethanol supercritical drying process is as follows: the aerogel is dried under the protection of nitrogen gas at a temperature of 260°C-320°C, the autoclave pressure is controlled at 8MPa-14MPa, and the reaction time is 4h-10h.
5. A low thermal conductivity, radiation resistant aerogel insulation felt, characterized in that: The low thermal conductivity and radiation resistant aerogel insulation felt prepared by the method for preparing the aerogel insulation felt according to any one of claims 1 to 4 has the following properties: Density: 0.16 g / cm 3 -0.19g / cm 3 , the thermal conductivity at room temperature is 0.01595W / (m·K)-0.01958W / (m·K), the thermal conductivity at 300℃ is 0.01971W / (m·K)-0.02878W / (m·K), and the thermal conductivity at 500℃ is 0.03752W / (m·K)-0.05594W / (m·K); After irradiation at 350℃ and γ-ray with cumulative dose of 1.0×10 6 After Gy irradiation, there is no change in appearance. The thermal conductivity at room temperature is 0.01602W / (m·K)-0.01619W / (m·K), the thermal conductivity at 300℃ is 0.02422W / (m·K)-0.02423 W / (m·K), and the thermal conductivity at 500℃ is 0.03789W / (m·K)-0.03799 W / (m·K).
Citation Information
Patent Citations
Rare-earth-based aerogel material with radiation shielding effect and heat insulation property as well as preparation and application of rare-earth-based aerogel material
CN110563435A
High-temperature resistant SiO2-Gd2O3 composite aerogel and its preparation method
CN112320833B
Cited By
Ultralow-thermal-conductivity silicon oxide aerogel heat insulation felt and preparation method thereof
CN120817778A
An ultralow thermal conductivity silicon oxide aerogel insulation felt and a preparation method thereof
CN120817778B